Business plan for Ade farm food production company NIG LTD - Aremu, Adejare Yusuff; Shola, Adediran Daud (International research journal of management, IT and social sciences, 2016)
Ade Farmers Food Production is a family farms business, it focuses to produce more food in quantity and to be packaging in a different kg, also to be added to the value of Nigeria economies and to contribute many benefits for communities. In addition, we have a plan to extend to many countries in Asia, like Malaysia, China, Dubai. Farmers Food production is one of the successful food farms. The idea behind the business is to provide healthy and delicious semovita and emails to the public. In addition to semovita and mails the company plans to produce and market manure compost garden amendment products. Farmers Food productions being formed from the family successful food farms, The latter has long-researched horticultural and agronomic techniques, as well as compost and land blending technology now being promoted by the farmer association of Oyo state agencies. The company is a combination of cutting edge, highest quality, and efficient food technology and production.